Exploring the Gender Gap in Tech Companies: Why Aren't There More Women? - Chaudhry, Haroon; Wall, Alison E.; Wall, Jerry L. (Competition Forum, 2019)
Diversity issues in organizations have long been the subject of organizational studies and cultural examinations. While organizations have made several advancements to balance the presence of female representation in their employees, there remains a paucity of women in certain fields, most notably the tech industry where, despite similar performance in courses, women are alarmingly underrepresented. This paper examines this lack of diversity and proposes some remedies for specifically addressing the lack of women in the tech industry and can be extended to participation in any STEM careers that makes up a significant portion of the tech industry.
Num Pages: 275-280 Place: Indiana, United States
Keywords: Bullying; Business And Economics; Careers; Employees; Employment; Females; Gender; High tech industries; Litigation; Multiculturalism & pluralism; Research & development–R&D; STEM education; STEM professions; Social networks; Success; Women; dept.mgt; peer-reviewed

A metacognitive approach to understanding what marker variables measure - Leonard, Stephanie; Simmering, Marcia J.; Wall, Alison E. (Current Psychology, 2024)
Marker variables provide an efficacious means of post hoc detection of common method variance (CMV) in data. These variables are measured in the same way as substantive variables, but because they are conceptually unrelated to the variables of interest, they are believed to be a proxy for CMV. Although marker variables have demonstrated effectiveness, questions remain as to what they actually measure, and thus, why they work. This lack of knowledge prevents researchers from choosing appropriate marker variables to include in same source surveys. The purpose of this research is to determine how four different marker variables account for common rater effects which can cause CMV. A metacognitive approach is used to develop an empirical study using two samples, with a focus on the specific rater effects of mood state, transient mood, consistency motif, and illusory correlations. Findings indicate that these marker variables elicit similar respondent reactions and do not create a notable psychological separation between substantive variables. Additionally, there is evidence that respondents’ use of consistency motifs and illusory correlations influence substantive variable relations. Finally, using the confirmatory factor analysis marker technique, data from two samples indicate the presence of CMV, but not bias from CMV, indicating that the problem of artificially inflated results due to CMV may be overstated.
Keywords: Common method variance; Marker variables; Metacognition; Survey research; dept.mgt; peer-reviewed

Employee Assistance Programs: Balancing Increased Productivity and Engagement Among Employees with Equal Employment and Legal Complience - Smith, Robert A.; Badr, Kauther S.; Wall, Alison E. (Competition Forum, 2019)
Managing the impact of employees' personal and work-related difficulties on workplace productivity is becoming increasingly salient for organizations. Employee Assistance Programs (EAPs) are one approach to help improve the quality of life for employees and maximize their productivity. While EAPs have many benefits, potential negative ramifications and legal considerations must also be considered. This article highlights some important cases and the best practices for organizations to utilize in creating clear organizational policies that align with equal employment opportunity and privacy laws in collaboration with legal and human resources professionals and employee assistance providers to reduce or eliminate potential liability.
Num Pages: 232-239 Place: Indiana, United States
Keywords: Absenteeism; Affirmative action; Business And Economics; Complaints; Confidentiality; Costs; Employees; Employers; Employment discrimination; Human resource management; Labor law; Performance evaluation; Productivity; Sexual harassment; dept.mgt; peer-reviewed; ⛔ No DOI found